Revitalization of Traditional Music through Digital Learning Media for Gambang Kromong 5.0 Innovation Study - Gusti Laskar Ferdiansyah Simatupang; Rien Safrina; Rizki Taufik Rakhman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This literature review analyzes the transformative potential of digital learning media in revitalizing Indonesian traditional music, with a particular focus on Gambang Kromong innovation within the framework of Society 5.0. Traditional music, as the foundation of cultural identity, faces significant threats from globalization and modernization, resulting in declining interest, especially among the younger generation. This approach examines how digital technologies can serve as a catalyst for the preservation, learning and dissemination of traditional music, transforming it from a marginalized status to one of contemporary relevance. The report synthesizes existing literature to identify key trends, benefits derived from the use of technologies such as Digital Audio Workstations (DAWs), Virtual Reality (VR), Augmented Reality (AR), Artificial Intelligence (AI), gamification, and online and social media platforms. In addition, the report discusses inherent challenges, including the digital divide, the need for increased educator competencies, and intellectual property rights issues, while highlighting opportunities for collaboration and global audience reach. The conceptualization of